2010
DOI: 10.3109/03009741003742763
|View full text |Cite
|
Sign up to set email alerts
|

Influence of female hormonal factors, in relation to autoantibodies and genetic markers, on the development of rheumatoid arthritis in northern Sweden: a case–control study

Abstract: A longer duration of breastfeeding increased the risk of developing RA, especially among individuals seropositive for ACPA or IgM-RF or carrying the PTPN22 1858T variant. Use of OC for ≥ 7 years was associated with a decreased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…After detailed evaluations, 10 studies were full-text reviewed and 4 studies were excluded (3 studies used duplicate data 17,18,19 and 1 had no relation to RA onset, but with severity of RA 20 ). Finally, in the current study, 6 eligible studies 11,12,13,14,15,16 that met the inclusion criteria were included in our metaanalysis. There were 5 studies on whites and 1 study on Asians.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…After detailed evaluations, 10 studies were full-text reviewed and 4 studies were excluded (3 studies used duplicate data 17,18,19 and 1 had no relation to RA onset, but with severity of RA 20 ). Finally, in the current study, 6 eligible studies 11,12,13,14,15,16 that met the inclusion criteria were included in our metaanalysis. There were 5 studies on whites and 1 study on Asians.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The Journal of on July 23, 2015 -Published by www.jrheum.org Downloaded from the influence of breastfeeding on the risk of RA have yielded conflicting results 11,12,13,14,15,16,17,18,19 12,13 . One proposed mechanism for this protective effect is through antiinflammatory progesterone, which rises during pregnancy and continues to be high during breastfeeding 24 .…”
Section: Rheumatologymentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk has been observed during the first 3 months up to 2 years post partum,3–6 whereas parous women in the long run seem to have no increased risk7–10 or even a reduced risk of RA 11–13. For other reproductive factors, such as number of children7–9 11 13 14 and age at first birth,7–9 11 12 the reported results are inconclusive. Notably, previous studies have been conducted without studying the two subsets of RA, which are characterised by the presence/absence of antibodies to citrullinated peptide antigens (ACPA), separately.…”
Section: Introductionmentioning
confidence: 97%
“…[42][43][44][45][46] The majority of studies have found that past or current use of COCs has a protective effect against RA development. 47 In a recent case-control study, Berglin et al 48 reported a decreased risk for development of RA in women who had been using COCs for 7 years or more (OR: 0.37; 95% CI: 0.15-0.93). In the Norfolk Arthritis Register, which is a primary care-based cohort of patients with recentonset inflammatory polyarthritis, it was found that COC users have a better functional outcome than nonusers.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%